Pemberdayaan Sosial dan Ekonomi pada Kelompok Penyandang Disabilitas Fisik di Kota Bandung - Ariel Pandita Dhairyya; Erna Herawati (Universitas Padjadjaran, 2019)
This study explores an economic and social empowerment activities by Kelompok Berani Binangkit (KBB), an informal organization for the people with disabilities in Bandung City. KBB activities focus on pegleg and pegarm production and selling to improve the members’s livelihood. KBB also has mission to donate pegleg and pegarm for the disabled who could not affort it. All of the KBB activities are initiated by the members.The study applies qualitative method; in particular case study model. Data were collected through participation observation towards KBB’s activities and in-depth interviews to its members. The study finds that the main purpose of KBB, that is to improve the livelihood of the members has not brought a significant impact to its members. The members’ income is relatively small and does not sufficient for their living. Meanwhile social empowerment activities has brought a significant impact to the member’s social lives. The KBB members build an emotional bond throught several ways such as spesific model of communication among them, and build self confidence as well as develop open-minded attitude regarding their physical condition and response towards negative stigma that attached to them. These have led KBB’s members construct their new identity, so they could feel ‘normal’.